Comparison of Ultrasound Versus Ultrasound with Nerve Stimulator-Guided Infraclavicular Block Anesthesia Methods in Pediatric Patients - Abdulhakim Şengel; Evren Büyükfirat; Selçuk Seçilmiş; Nuray Altay; Ahmet Atlas; Abdullah Şengül (Medicina)
Background and objectives: Brachial plexus block is one of the most effective anesthesia and analgesia methods for upper extremity surgeries across different age groups. However, the number of studies on this block in children is insufficient. The aim of this study was to retrospectively analyze and discuss the efficacy and safety of ultrasound (US)- and Ultrasound with nerve stimulator (US + NS)-guided infraclavicular brachial plexus block (ICB) in pediatric patients. Materials and Method: In this study, we retrospectively analyzed the data of 240 pediatric patients admitted to our clinic between October 2020 and April 2023, 120 of whom underwent US-guided ICB and 120 who underwent US + NS-guided ICB. Results: Demographic data of both groups who underwent US and US + NS-guided ICB were similar. The mean procedure time was 6.1 ± 0.8 min for the US group and 8.31 ± 0.82 min for the US + NS group (p < 0.001). The mean operative time was 62.4 ± 11.3 min in the US group and 62.4 ± 9.5 min in the US + NS group (p = 0.73). Intraoperative and postoperative opioid and additional analgesia use and pain scores at 1, 3, 6, 9, 12, 15, and 24 h were recorded in both groups. The mean duration of the motor block (MBD) was 6.20 ± 0.95 h in the US group and 6.29 ± 0.88 h in the US + NS group (p = 0.46). The mean duration of sensory block (SBD) was 9.38 ± 2.13 h in the US group and 9.53 ± 2.05 h in the US + NS group (p = 0.38). Conclusions: In pediatric patients, US and US + NS-guided ICB applications are effective and safe in ease of application, prolonged analgesia, and low complication rates. In skilled hands, US-guided ICB can be as effective as US + NS-guided ICB. Further prospective studies with more significant patient populations are needed to validate these findings.